Ground level concentration of some air pollutants from Nigeria thermal power plants - A. J, Adesanmi; Bamidele Sunday, Fakinle; Jamiu Adetayo, Adeniran; Rafiu Olasunkanmi, Yusuf (Taylor & Francis, 2023)
International journal of taylor&francis,vol38,no16,pg2426-2432